Leading the charge : leadership lessons from the battlefield to the boardroom - Zinni, Anthony C.; Koltz, Tony (New York, United States : Palgrave Macmillan, 2009)
A retired general examines the leadership challenges of the twenty-first century, addressing outdated practices while citing the importance of tapping the potential of rapidly changing technologies
Includes index
BSBA
Keywords: Leadership